Preparation method of enrichment type noble metal catalyst and application thereof in preparation of allyl acetate
Patent Information
- Application Number
- CN202310012575.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-01-05
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2043-01-05
AI Technical Summary
[0008]现有技术难以解决用于气态丙烯、醋酸和氧生成醋酸烯丙酯反应的催化剂活性和选择性低的问题,制约了醋酸烯丙酯的高效生产
[0038]1)本发明通过二羟基丙酮处理载体,使载体表面的羟基更加丰富,在浸渍沉淀过程中能使减缓碱液向内部扩散,从而形成更富集的贵金属分布;催化剂的过程中引入第二种金属钽。与现有催化剂制备技术相比,本发明的贵金属催化剂在较窄范围内的富集分布,其在催化气态丙烯、醋酸和氧气的反应过程的初期,有更高的选择性和催化活性;催化剂的稳定性更高,在反应过程中催化剂活性下降更慢。
Smart Images

Figure BDA0004038212030000061 
Figure HDA0004038212040000011 
Figure HDA0004038212040000012
Abstract
Description
Technical Field
[0001] This invention relates to a method for preparing enriched noble metal catalysts and their use in the reaction of gas-phase propylene, acetic acid and oxygen to produce allyl acetate. Background Technology
[0002] In 1968, Bayer first developed a method for producing vinyl acetate from gaseous ethylene, acetic acid, and oxygen. Due to its simple process, high production capacity, and good catalyst stability, it has been refined and optimized by numerous companies over the past 60 years, and the Bayer process has now become the mainstream technology for vinyl acetate production. The Bayer process uses supported noble metal catalysts, with Pd and Au as the active components and SiO2 as the support. Specifically, in a fixed-bed tubular reactor, a mixture of ethylene, acetic acid, oxygen, and nitrogen passes through the catalyst.
[0003] US Patent 3830834 discloses a method for the continuous production of vinyl acetate from gaseous ethylene and acetic acid under oxygen conditions. The catalyst consists of palladium and alkali metal acetates and noble metals selected from gold, iridium, ruthenium, platinum, rhodium and osmium. By introducing alkali metal acetates during operation, continuous operation can be achieved for more than 6 months.
[0004] German patent DE102007025362 discloses a method for preparing a shell catalyst for producing vinyl acetate monomer. The catalyst support has a shell containing Pd and Au, and the noble metal catalyst is relatively uniformly distributed in the area of 90% of the shell thickness.
[0005] Japanese Patent JP2008080326 discloses a method for manufacturing a catalyst for producing alkenyl acetate, which achieves close loading of Pd and Au together, thereby improving the activity and selectivity of the catalyst.
[0006] The reaction of gaseous propylene, acetic acid and oxygen to form allyl acetate is similar to the reaction of gaseous ethylene, acetic acid and oxygen to form vinyl acetate. It is well known that a supported noble metal "eggshell" catalyst is required. The reaction gas is introduced into a tubular fixed bed reactor and the heat released by the reaction is removed by high-pressure boiling water.
[0007] The difference between propylene oxyacylation and ethylene oxyacylation is that the catalyst life of propylene oxyacylation is about 12 months, which is less than the 2 to 3 years of ethylene oxyacylation; the STY value of the target product per liter of catalyst per unit time is also less than that of ethylene oxyacylation; and the product selectivity is also lower than that of ethylene oxyacylation.
[0008] Existing technologies struggle to address the low catalyst activity and selectivity in the reaction of gaseous propylene, acetic acid, and oxygen to produce allyl acetate, hindering the efficient production of allyl acetate. Furthermore, catalyst deactivation due to precious metal particle agglomeration increases the cost of catalyst use. Therefore, mitigating the decline in catalyst activity has become a key concern for researchers. Summary of the Invention
[0009] The "eggshell" type noble metal catalysts well-known in the art are characterized by a distribution where all the noble metal elements are located in the outer region of the support. Based on this, the present invention aims to provide a method for preparing a more concentrated noble metal catalyst, in which the active component, the noble metal, is concentrated in a narrower region of the catalyst "eggshell," resulting in higher activity and selectivity in the catalytic propylene oxyacylation reaction, and a slower decline in activity.
[0010] To achieve the above objectives, the technical solution adopted by the present invention is as follows:
[0011] An enriched noble metal catalyst, the catalyst comprising a support, an active component, and an additive;
[0012] The support is mainly composed of SiO2, which can be derived from natural bentonite or artificially synthesized gaseous SiO2 by pyrolysis. The mass fraction of SiO2 in the support is greater than 80%, preferably greater than 90%, and more preferably greater than 95%. The support may contain a small amount of Al2O3, with a mass fraction of less than 10%, and more preferably less than 5%.
[0013] The carrier can be spherical, ellipsoidal, solid cylindrical, hollow cylindrical, etc., preferably ellipsoidal, with an equivalent diameter in the range of 2 to 8 mm, preferably in the range of 3 to 6 mm.
[0014] The active components include (a) palladium and (b) tantalum;
[0015] Preferably, the mass fraction of palladium is 0.5% to 5%, more preferably 0.5% to 2%; the mass fraction of tantalum is 0.15% to 5%, more preferably 0.15% to 2%, based on the carrier mass.
[0016] The additive is an alkali metal salt, preferably a carboxylate, more preferably an acetate; the alkali metal is at least one of lithium, sodium, potassium, rubidium, and cesium, more preferably sodium and potassium; the mass fraction of the alkali metal salt is 1-20%, more preferably 5-15%, based on the carrier mass.
[0017] The method for preparing the catalyst according to the present invention includes the following steps:
[0018] Step 1: Pretreatment of the carrier with dihydroxyacetone in a hydrothermal reactor;
[0019] Step 2: The salt solution containing the active component is uniformly brought into contact with the carrier to obtain intermediate A;
[0020] Step 3: Aging the obtained intermediate A in a sealed environment;
[0021] Step 4: Convert the ionic form of the active component into its corresponding insoluble state, reduce, and dry to obtain intermediate B;
[0022] Step 5: Contact the alkali metal salt with the intermediate B obtained in the previous step evenly, and dry to obtain the catalyst product.
[0023] In the method described, step 1 involves pretreating the carrier with dihydroxyacetone in a hydrothermal reactor, which enriches the number of hydroxyl groups on the carrier surface. Specifically, the carrier is placed in a hydrothermal reactor, and a certain amount of 5-15 wt% dihydroxyacetone (which can be a monomer or its dimer) aqueous solution is added to cover the carrier. The reactor is then treated at 80-120°C, preferably 90-120°C; the treatment time is 4-24 hours, preferably 8-24 hours, more preferably 16-24 hours; and the treatment pressure is 0.5 MPa or higher, preferably 0.5-2.5 MPa.
[0024] The specific surface area of the treated carrier is 40–400 m². 2 / g, preferably 40-300m 2 / g, more preferably 40-250m 2 / g; the pore volume of the carrier is 0.2-1.2 mL / g, preferably 0.2-1.0 mL / g, more preferably 0.2-0.8 mL / g; the average pore size of the carrier is 5-17 nm, preferably 7-17 nm, more preferably 9-17 nm.
[0025] The number of hydroxyl groups on the support surface was determined using thermogravimetric analysis (TGA). First, the weight loss of the support before treatment was obtained between 120 and 180 °C, and the data was calibrated using LiAlH4 titration. Then, the weight loss and specific surface area of the support after treatment were measured between 120 and 180 °C using a programmed temperature rise method. The silanol content on the surface after treatment was found to be 2–10 OH / nm. 2 Preferably 3-5 OH / nm 2 .
[0026] In step 2, the prepared salt solution containing the active component is uniformly brought into contact with the carrier after the above treatment. The salt solution is selected from the soluble salt solution of the active component, and it is necessary to ensure that the salt solution is uniformly distributed on the carrier microspheres.
[0027] In step 3, the above intermediates are treated in a closed nitrogen environment at a temperature of 20–40°C, a pressure of 0.5–1.5 MPa, and an aging time of 4–24 hours.
[0028] In step 4, the ionic form of the active component is converted into its corresponding insoluble state, for example, by reacting a metal salt with a precipitating agent. Precipitating agents that convert metal ions into precipitates are preferably sodium hydroxide, potassium hydroxide, sodium carbonate, potassium carbonate, etc., and more preferably sodium hydroxide and sodium carbonate.
[0029] The reducing agent used for reduction can be hydrogen, propylene, ethylene, hydrazine, etc., with hydrogen and propylene being preferred. For example, in a hydrogen atmosphere, the pressure is 0.5 to 1.5 MPa, and the reduction time is 4 to 24 hours.
[0030] The active metal precipitate can be partially reduced to its elemental form through reduction operations. The noble metal palladium can exist as a pure element or as a mixture of element and oxide. Tantalum exists as an oxide.
[0031] In step 5, the alkali metal salt is brought into uniform contact with the intermediate obtained in the previous step, for example, by immersing the intermediate in an alkali metal salt solution and drying it to prepare an enriched noble metal catalyst.
[0032] After cutting the catalyst in half, it can be seen that the active components are distributed in the "eggshell" region of the support. The thickness of the "eggshell" observed under a high magnification microscope is 50-500 μm, preferably 100-400 μm.
[0033] Using scanning electron microscopy to obtain an energy dispersive spectroscopy (EDS) spectrum of the noble metal distribution, it was found that palladium was concentrated in a narrow region of the "eggshell," located in the middle of the eggshell. The width of this region was less than or equal to 50 μm, preferably less than 40 μm, and more preferably less than 30 μm. The palladium metal distributed in this narrow region accounted for more than 60% of the total amount added, preferably more than 70%, and more preferably more than 80%.
[0034] This invention also relates to the application of the above-mentioned catalyst in the preparation of olefinic acetate.
[0035] A method for preparing an olefinic acetate comprises: preparing an olefinic acetate from acetic acid, oxygen, and a gaseous olefin in the presence of the enriched noble metal catalyst described above; wherein the gaseous olefin is preferably gaseous propylene.
[0036] In one embodiment, acetic acid, oxygen, and gaseous propylene feedstock are fed into a reactor packed with the catalyst described in this invention. The feedstock, in molar ratio, is gaseous propylene:acetic acid:oxygen:water = 1:(0.1-0.5):(0.1-0.5):(0.2-1.0). The reaction is carried out at 120-180°C and 0.5-1.0 MPaG, with a total feed gas volume hourly space velocity of 1000-3000 h⁻¹. -1 Allyl acetate was prepared.
[0037] The present invention has the following beneficial effects:
[0038] 1) This invention treats the support with dihydroxyacetone, enriching the hydroxyl groups on the support surface. This slows down the diffusion of alkali solution into the interior during the impregnation and precipitation process, resulting in a more concentrated distribution of noble metals. A second metal, tantalum, is introduced during the catalyst preparation process. Compared with existing catalyst preparation technologies, the noble metal catalyst of this invention exhibits a narrower enrichment distribution and higher selectivity and catalytic activity in the initial stage of the reaction of gaseous propylene, acetic acid, and oxygen. The catalyst also demonstrates higher stability and a slower decline in activity during the reaction. Attached Figure Description
[0039] Figure 1 This is an optical microscope image of the distribution of the active component Pd in the catalyst obtained in Example 1;
[0040] Figure 2 This is the energy spectrum of the noble metal Pd in the catalyst obtained in Example 1. Detailed Implementation
[0041] The present invention will be further illustrated below with specific embodiments. These embodiments are merely illustrative and do not limit the scope of the invention.
[0042] The calculation and testing methods used in the examples or comparative examples are as follows:
[0043] 1. Gas chromatography was used, employing an Agilent GC 8890A chromatograph, to analyze the content of each component in the reaction products, and the catalyst activity was calculated using the following formula:
[0044]
[0045] 2. Methods for determining the specific surface area and pore structure information of catalysts
[0046] The specific surface area of the catalyst was determined by the BET method, the pore structure by the N2 physical adsorption method, and the pore volume by the BJH desorption method. The testing instrument was a Micromeritics ASAP 2460.
[0047] 3. Determination of the location and thickness of the active component in the catalyst
[0048] The catalyst was divided in half using a slicer to obtain a cross-section of the catalyst. The location and thickness of the active components of the catalyst were determined using a Zeiss Axiolab 5 optical microscope.
[0049] 4. Energy spectrum of Pd distribution, an active component of the catalyst
[0050] The catalyst was encapsulated in epoxy resin and aged under high temperature and light for 48 hours. The catalyst was then polished with sandpaper until its maximum cross-sectional area was exposed. Elemental analysis was performed using a wavelength dispersive detector with a JEOL JXA-8100 at an accelerating voltage of 15 kV, an irradiation current of 0.03 μA, and a step size of 1.5 μm.
[0051] The distribution intensity of palladium in the catalyst is obtained by line scanning, the total area is obtained by integration, the enrichment zone area is obtained by integrating the peaks at the enrichment points, and then the palladium content at the enrichment zone position is calculated.
[0052]
Example 1
[0053] 635g of silica gel spheres were placed in a hydrothermal reactor, and 1200mL of a 10wt% dihydroxyacetone solution was added. The reactor was treated at 120℃ for 20 hours at a pressure of 0.5MPa. After treatment, the silica gel spheres were removed. The average particle size of the treated carrier was 4.1mm, and the specific surface area was 141m². 2 / g, pore volume is 0.35mL / g, average pore size is 10.5nm;
[0054] Prepare 1 L of an aqueous solution of sodium chloropalladium and tantalum chloride containing 5.0 g Pd and 1.5 g Ta, stir thoroughly, and then add it to silica gel beads. Let stand for 2 h to obtain intermediate 1. Transfer intermediate 1 to a 5 L hydrothermal reactor, replace the air in the reactor with nitrogen, increase the pressure to 0.75 MPa, and treat at 25 °C for 15 h to obtain intermediate 2. Then add 2 L of 0.4 mol / L sodium hydroxide solution to obtain intermediate 3. Reduce intermediate 3 at 100 °C under a hydrogen atmosphere. After reduction, wash the free chlorine on the catalyst surface with deionized water, and then dry at 120 °C for 4 h to obtain intermediate 4. Impregnate intermediate 4 with a solution containing 50 g potassium acetate and dry at 120 °C for 4 h to obtain catalyst 1.
[0055] Analysis showed that the palladium content in the enriched area of the active component was 85% of the total content, the enrichment band width was 28 μm, and the total eggshell thickness was 302 μm.
[0056] Catalyst performance testing:
[0057] The reaction temperature was 150℃, the reaction pressure was 0.8 MPaG, and the volume hourly space velocity was 2500 h⁻¹. -1 The raw material composition was propylene:acetic acid:oxygen:water = 1:0.3:0.25:0.35. Samples were taken and analyzed after 50 hours of initial catalyst operation. The catalyst activity was 456 g / L / h, and the allyl acetate selectivity was 96.2%. After 6000 hours of operation in the activity evaluation device, the catalyst activity remained at 442 g / L / h, and the allyl acetate selectivity remained as high as 96.0%.
[0058]
Example 2
[0059] 628g of silica gel spheres were placed in a hydrothermal reactor, and 1180mL of a 10wt% dihydroxyacetone solution was added. The reactor was treated at 100℃ for 20 hours at a pressure of 0.75MPa. After treatment, the silica gel spheres were removed. The average particle size of the treated carrier was 4.8mm, and the specific surface area was 165m². 2 / g, pore volume is 0.47mL / g, average pore size is 12.5nm;
[0060] Prepare 1 L of an aqueous solution of sodium chloropalladium and tantalum chloride containing 4.5 g Pd and 1.5 g Ta, stir thoroughly, and then add it to silica gel beads. Let it stand for 2 h to obtain intermediate 1. Transfer intermediate 1 to a 5 L hydrothermal reactor, replace the air in the reactor with nitrogen, increase the pressure to 0.75 MPa, and treat at 25 °C for 18 h to obtain intermediate 2. Then add 2 L of 0.4 mol / L sodium hydroxide solution to obtain intermediate 3. Reduce intermediate 3 at 100 °C under a hydrogen atmosphere. After reduction, wash the free chlorine on the catalyst surface with deionized water, and then dry at 120 °C for 4 h to obtain intermediate 4. Impregnate intermediate 4 with a solution containing 60 g potassium acetate and dry at 120 °C for 4 h to obtain catalyst 2.
[0061] Analysis showed that the palladium content in the enriched area of the active component was 76% of the total content, the enrichment band width was 42 μm, and the total eggshell thickness was 460 μm.
[0062] Catalyst performance testing:
[0063] The reaction temperature was 150℃, the reaction pressure was 0.8 MPaG, and the volume hourly space velocity was 2500 h⁻¹. -1 The raw material composition was propylene:acetic acid:oxygen:water = 1:0.3:0.25:0.35. Samples were taken and analyzed after 50 hours of initial catalyst operation. The catalyst activity was 364 g / L / h, and the allyl acetate selectivity was 94.6%. After 6000 hours of operation in the activity evaluation device, the catalyst activity was 325 g / L / h, and the allyl acetate selectivity was 95.3%.
[0064]
Example 3
[0065] 585g of silica gel spheres were placed in a hydrothermal reactor, and 1120mL of a 10wt% dihydroxyacetone solution was added. The reactor was treated at 110℃ for 16 hours at a pressure of 0.95MPa. After treatment, the silica gel spheres were removed. The average particle size of the treated carrier was 4.5mm, and the specific surface area was 128m². 2 / g, pore volume is 0.37mL / g, average pore size is 14.3nm;
[0066] Prepare 1 L of an aqueous solution of sodium chloropalladium and tantalum chloride containing 5.5 g Pd and 1.8 g Ta, stir thoroughly, and then add it to silica gel beads. Let stand for 2 h to obtain intermediate 1. Transfer intermediate 1 to a 5 L hydrothermal reactor, replace the air in the reactor with nitrogen, increase the pressure to 0.75 MPa, and treat at 25 °C for 18 h to obtain intermediate 2. Then add 2 L of 0.4 mol / L sodium hydroxide solution to obtain intermediate 3. Reduce intermediate 3 at 100 °C under a hydrogen atmosphere. After reduction, wash the free chlorine on the catalyst surface with deionized water, and then dry at 120 °C for 4 h to obtain intermediate 4. Impregnate intermediate 4 with a solution containing 30 g potassium acetate and dry at 120 °C for 4 h to obtain catalyst 3.
[0067] Analysis showed that the palladium content in the enriched area of the active component was 63% of the total content, the enrichment band width was 50 μm, and the total eggshell thickness was 431 μm.
[0068] Catalyst performance testing:
[0069] The reaction temperature was 150℃, the reaction pressure was 0.8 MPaG, and the volume hourly space velocity was 2500 h⁻¹. -1 The raw material composition was propylene:acetic acid:oxygen:water = 1:0.3:0.25:0.35. Samples were taken and analyzed after 50 hours of initial catalyst operation. The catalyst activity was 314 g / L / h, and the allyl acetate selectivity was 93.2%. After 6000 hours of operation in the activity evaluation device, the catalyst activity was 306 g / L / h, and the allyl acetate selectivity was 93.1%.
[0070] Comparative Example 1
[0071] The support is not treated during the catalyst preparation process.
[0072] 635g of untreated carrier was taken, with an average particle size of 4.2mm and a specific surface area of 234m². 2 / g, with a pore volume of 0.57mL / g and an average pore size of 9.3nm, a 1L aqueous solution of sodium chloropalladium and tantalum chloride containing 5.0gPd and 1.5gTa was prepared, stirred thoroughly, and directly contacted with silica gel balls. After standing for 2 hours, the remaining operations were the same as in Example 1 to obtain catalyst 4.
[0073] Analysis showed that the palladium content in the enriched area of the active component was 59% of the total content, the enrichment band width was 78 μm, and the total eggshell thickness was 369 μm.
[0074] Catalyst performance evaluation:
[0075] The reaction temperature was 150℃, the reaction pressure was 0.8 MPaG, and the volume hourly space velocity was 2500 h⁻¹. -1The raw material composition was propylene:acetic acid:oxygen:water = 1:0.3:0.25:0.35. Samples were taken and analyzed after 50 hours of initial catalyst operation. The catalyst activity was 309 g / L / h, and the allyl acetate selectivity was 92.9%. After 6000 hours of operation in the activity evaluation device, the catalyst activity was 226 g / L / h, and the allyl acetate selectivity was 90.8%.
Claims
1. An enriched noble metal catalyst, said catalyst comprising a support, an active component, and an additive; The main component of the support is SiO2, and the mass fraction of SiO2 in the support is greater than 80%. The active components include palladium and tantalum; The mass fraction of palladium is 0.5%–5%, and the mass fraction of tantalum is 0.15%–5%, based on the mass of the carrier; The additive is an alkali metal salt; the alkali metal is at least one selected from lithium, sodium, potassium, rubidium, and cesium. The mass fraction of the additives is 1-20%, based on the carrier mass; The preparation method of the enriched noble metal catalyst includes the following steps: Step 1: Pretreatment of the carrier with dihydroxyacetone; Step 2: The salt solution containing the active component is uniformly brought into contact with the carrier to obtain intermediate A; Step 3: Aging the obtained intermediate A in a sealed environment; Step 4: Convert the ionic form of the active component into an insoluble state, reduce it, and dry it to obtain intermediate B; Step 5: Bring the alkali metal salt into uniform contact with intermediate B and dry to obtain the catalyst product.
2. The catalyst according to claim 1, wherein, The alkali metal salt is a carboxylate; the mass fraction of the auxiliaries is 5-15%.
3. The catalyst according to claim 2, wherein, Alkali metal salts are acetates.
4. The catalyst according to claim 1, wherein, In step 1, the sample is treated in a hydrothermal reactor at 80–120°C for 4–24 hours at a pressure of 0.5–2.5 MPa.
5. The catalyst according to claim 1 or 4, wherein, In step 1, the specific surface area of the treated carrier is 40–400 m². 2 / g, pore volume is 0.2~1.2mL / g, and average pore size is 5~17nm.
6. The catalyst according to claim 1, wherein, In step 3, the temperature is 20–40℃ and the aging time is 4–24 hours.
7. The catalyst according to claim 1, wherein, In step 4, the active component is converted into an insoluble state by precipitating the metal salt with the precipitant.
8. The catalyst according to claim 7, wherein, In step 4, the precipitant is selected from sodium hydroxide, potassium hydroxide, sodium carbonate, and potassium carbonate.
9. The catalyst according to claim 1, wherein, In step 4, the reducing agent used for reduction is selected from hydrogen, propylene, ethylene, and hydrazine.
10. The use of the catalyst according to any one of claims 1-9 in the preparation of olefinic acetate.
11. A method for preparing an olefinic acetate, comprising: Acetic acid esters are prepared from acetic acid, oxygen, and gaseous olefins in the presence of the enriched noble metal catalyst as described in any one of claims 1-9.
12. The preparation method according to claim 11, wherein, The olefin is propylene.
13. The preparation method according to claim 11 or 12, wherein, The molar ratio of gaseous olefin:acetic acid:oxygen:water = 1:(0.1-0.5):(0.1-0.5):(0.2-1.0) was used for the reaction at 120-180℃ and 0.5-1.0 MPaG, with a total feed gas volume hourly space velocity of 1000-3000 h⁻¹. -1 .
Citation Information
Patent Citations
doped Pd / Au shell catalyst, process for its production and its use
DE102007025362A1
Method for manufacturing alkenyl acetate manufacturing catalyst
JP2008080326A
Process for the continuous preparation of vinyl acetate
US3830834A
Acetyl oxidation catalyst, preparation method thereof and method for preparing allyl acetate
CN114345369A
No title available
GB1266624A